Unchartered territory: Large-scale asset purchases by the European Central Bank - Kerstin Bernoth; Philipp König; Carolin Raab; Marcel Fratzscher (DIW Economic Bulletin, 2015)
The European Central Bank (ECB) decided at its Council meeting in January to implement a comprehensive program to purchase bonds, including euro area government bonds. The purchases are intended to anchor the rate of inflation and inflation expectations at below but close to two percent again. Given the lack of experience with this unconventional monetary policy instrument, the ECB is venturing into uncharted territory. Market expectations that the ECB would implement an additional round of monetary easing to fulfill its mandate have, in recent months, contributed to a further fall in interest rates and a depreciation of the euro. Since interest rates in the euro area are already very low and the current weak price development is also affected by factors that are difficult to influence through monetary policy, the further effectiveness of the bond purchase program is uncertain. In particular, its success depends largely on its impact on consumption and investment. At the same time, this kind of unconventional monetary policy measure also involves certain risks. The present report describes the current development of inflation in the euro area and outlines the main reasons for the recent decline in prices. It also discusses the transmission channels of a bond purchasing program, their possible relevance for the euro area, and potential risks associated with the program.
Keywords: E5; E58; E6; 330; monetary policy; large-scale asset purchases; quantitative easing; inflation